(1R, 2S, 6R)-Papayanal: a new male-specific volatile compound released by the guava weevil Conotrachelus psidii (Coleoptera: Curculionidae). Issue 5 (3rd May 2016) - Romero-Frías, Alicia; Murata, Yasuhiro; Simões Bento, José Maurício; Osorio, Coralia
Abstract: The guava weevil, Conotrachelus psidii is an aggressive pest of guava ( Psidium guajava L.) that causes irreparable damages inside the fruit. The volatile compounds of male and female insects were separately collected by headspace solid-phase microextraction or with dynamic headspace collection on a polymer sorbent, and comparatively analyzed by GC–MS. (1 R, 2 S, 6 R )-2-Hydroxymethyl-2, 6-dimethyl-3-oxabicyclo[4.2.0]octane (papayanol), and (1 R, 2 S, 6 R )-2, 6-dimethyl-3-oxabicyclo[4.2.0]octane-2-carbaldehyde (papayanal) were identified (ratio of 9:1, respectively) as male-specific guava weevil volatiles. Papayanal structure was confirmed by comparison of spectroscopic (EIMS) and chromatographic (retention time) data with those of the synthetic pure compound. The behavioral response of the above-mentioned compounds was studied in a Y-tube olfactometer bioassay, and their role as aggregation pheromone candidate components was suggested in this species. Graphical abstract: : C. psidii male-specific volatiles collected by DHS and HS-SPME.